Partograph Utilization and Associated Factors among Obstetric Care Providers Working in Public Health Facilities of Wolaita Zone, 2017 - Mesfin Markos; Aseb Arba; Kebreab Paulos (Hindawi Limited, 2020)
Background. Obstructed or prolonged labor is a major cause of maternal deaths. Prolonged and obstructed labor contributed to 13% of global maternal deaths which can be reduced by proper utilization of a partograph during labor. Obstetric caregivers' use of the partograph during labor has paramount importance in identifying any deviation during labor. Even though partograph use is influenced by different factors as obtained from the literatures, the magnitude of partograph utilization and the factors associated with its use are not well determined in the health facilities of Wolaita Zone. Objective. To assess the magnitude of partograph utilization and factors that affect its utilization among obstetric caregivers in public health facilities of Wolaita Zone, Ethiopia, 2017. Methods. An institution-based cross-sectional study was conducted on obstetric caregivers. A pretested and structured questionnaire was used to collect data. Data was entered to EpiData version 3.01 and exported to SPSS version 23.0 for further analysis. Logistic regression analyses were used to see the association of different variables. Result. A total of 269 obstetric caregivers participated in the study. Among those who were utilizing the partograph, 193 (71.7%) routinely used it for all laboring mothers and 76 (28.3%) of participants reported that they do not routinely utilize it. Greater number of service years (AOR=4.93, 95% CI: 1.53-15.88), on-the-job training (AOR=0.16, 95% CI: 0.06-0.43), good knowledge (AOR=3.35, 95% CI: 1.61-6.97), and favorable attitude towards partograph utilization (AOR=2.99, 95% CI: 1.28-7.03) were significantly associated with partograph utilization. Conclusion and Recommendation. Partograph utilization among obstetric caregivers in the public health facilities was good. Greater years of work experience, in-service training, having good knowledge, and favorable attitude towards partograph utilization among obstetric caregivers independently determined partograph utilization. Provision of on-the-job training to make obstetric caregivers improve knowledge and skill on partograph utilization, maintaining caregivers' retention to decrease turnover by providing different incentives to more experienced obstetric care providers, and establishing favorable attitude could improve the proper use of the tool.